The relationship between alexithymia characteristics in alcohol dependence and anxiety, social anxiety, self-esteem and adult attention-deficit hyperactivity symptoms: a comparative study - Mortan Sevi, Oya; Genç, Yasin; Odabaşıoğlu, Gürkan; Soykal, İlkay and Öztürk, Özgür (Journal of Dependence, 2014)
Objective: The aim of this study is to evaluate the alexithymia characteristics of inpatients and outpatients who were treated in Surp Pırgic Armenian Hospital Psychiatry Clinic and to observe the relationship between these charactheristics and anxiety, social anxiety, self-esteem, adult attention deficit symptoms, and also to compare these measures with nondependent controls. Method: The sample is consisted of 14 inpatients and outpatients who were treated in Surp Pırgic Armenian Hospital Psychiatry Clinic between the age of 1855 and 11 healthy controls who have not been diagnosed of alcohol and substance dependence or abuse. The participants were assessed using Michigan Alcoholism Screening Test, Toronto Alexithymia Scale, Rosenberg Self-Esteem Scale, Beck Anxiety Scale, Liebowitz Social Anxiety Scale, and also Wender-Utah Attention Deficit and Hyperactivity Disorder Rating Scale. The data obtained from experimental group and control group have been analysed with Mann Whitney-U Test and Spearman’s Rank Order Correlation Test. Results: It has been found out that the patients with alcohol dependence had higher alexithymia and adult attention deficit scores than the healthy controls. The patientswith alcohol dependence diagnosed as alexithymic had higher anxiety and social anxiety scores than nonalexithymics. Conclusion: The results above were supported with the literature findings. These results have been discussed in the light of the literature.